Effect of Osimertinib in Combination With Chemotherapy and Bevacizumab for Untreated Epidermal Growth Factor Receptor–Mutated Advanced Non-Small-Cell Lung Cancer: Case Report - Qin, Haifeng; Wang, Fang; Zeng, Zhen; Jia, Suting; Liu, Yuan; Gao, Hongjun (Frontiers in Pharmacology, 2021)
Introduction: Osimertinib is an oral, third-generation, irreversible epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) that selectively inhibits both EGFR-TKI–sensitizing and EGFR T790M resistance mutations. However, whether patients with EGFR mutations can be treated in combination with conventional therapies, such as chemotherapy, remains unknown. Case presentation: We treated a 67-year-old female diagnosed with non-small-cell lung cancer with an EGFR 21 exon L858R–positive mutation. The patient was treated with 80 mg orally administered osimertinib daily, 830 mg pemetrexed, 120 mg cisplatin, and 500 mg bevacizumab. After two cycles of therapy, the patient’s intrapulmonary lesions shrank from 18 × 24 mm to 16 × 4 mm. Moreover, two cycles of evaluation were PR, and four cycles of confirmation were PR. The patient continued to receive the treatments and tolerated them well. Conclusion: The patient benefited from treatment with osimertinib in combination with chemotherapy and bevacizumab.